2021
DOI: 10.3390/molecules26102978
|View full text |Cite
|
Sign up to set email alerts
|

Lupeol Accumulation Correlates with Auxin in the Epidermis of Castor

Abstract: Lupeol, a natural lupane-type pentacyclic triterpene, possesses various pharmacological properties, and its production attracts attention. Significant quantities of lupeol are deposited on the castor aerial organ surface and are easily extractable as a predominant wax constituent. Thus, castor might be considered as a potential bioreactor for the production of lupeol. The lupeol biosynthesis pathway is well known, but how it is regulated remains largely unknown. Among large numbers of castor cultivars, we targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Except for tomatoes, our findings imply that ZF-HD/ZHD family genes have been largely conserved in evolution, along with their functions. In previous studies of ZF-HD/ZHD genes in other plants, researchers have concluded that these genes have undergone severe purifying selection, and their functions cannot be differentiated [ 42 , 48 , 49 , 50 , 51 , 52 ]. Motif analysis showed various conserved motifs of ZmZHD proteins in Classes I and II, revealing similar motifs present in the same subclass in the phylogenetic tree that are functionally similar ( Figure 3 A,C).…”
Section: Discussionmentioning
confidence: 99%
“…Except for tomatoes, our findings imply that ZF-HD/ZHD family genes have been largely conserved in evolution, along with their functions. In previous studies of ZF-HD/ZHD genes in other plants, researchers have concluded that these genes have undergone severe purifying selection, and their functions cannot be differentiated [ 42 , 48 , 49 , 50 , 51 , 52 ]. Motif analysis showed various conserved motifs of ZmZHD proteins in Classes I and II, revealing similar motifs present in the same subclass in the phylogenetic tree that are functionally similar ( Figure 3 A,C).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 217 revealed the ultrahigh production of oleanolic acid in the shoot of Achyranthes bidentata of 371.8 mg L −1 , a 5.4-fold increase compared to the control after 2 days treatment of 0.2 mM MeJA, while the AbHMGR gene was expressed at a higher level, which suggested that oleanolic acid production may be the result of the up-regulated expression of AbHMGR . Additionally, auxin, 218 SA, 219 and GA 220 were also reported to regulate the HMGR gene, thus affecting the biosynthesis of pentacyclic triterpenoids. FPS is a key enzyme that regulates the synthesis of terpenoid precursors such as IPP and DMAPP in the MVA pathway.…”
Section: Biosynthetic Pathways and Transcriptional Regulation Of Pent...mentioning
confidence: 99%
“…A transcriptome analysis showed that several auxin-related genes have different patterns of expression in the hypocotyl, characterized by a low level of lupeol, and stem internodes, with a high level of lupeol, suggesting that auxin might be implied in the regulation of lupeol biosynthesis. Furthermore, several auxin-responsive cis-elements are found in promoter regions of two key enzymes involved in lupeol production (RcHMGR and RcLUS), of which the expression seemed to be induced by auxin treatments, and lupeol content was reported to be increased by auxin treatment and decreased by auxin transport inhibition [120]. Wang et al [121] have identified a glutathione peroxidase gene family in the genome of R. communis.…”
Section: New Breeding Techniques For Oleaginous Crops: Gmo Technology...mentioning
confidence: 99%